Bridging the Digital Divide: Technology Adoption among College Teachers in Khyber Pakhtunkhwa - Ali, Shahid; Usman, Palwasha (The Lighthouse Journal of Social Sciences, 2024)
This study investigates the adoption and integration of online applications in college-level teaching among faculty members in public sector colleges of Khyber Pakhtunkhwa, Pakistan. Utilizing a descriptive survey design, data were collected from 447 Lecturers, Assistant Professors, and Associate Professors across multiple districts. The research explores faculty access to internet and digital tools, their usage patterns, and the extent to which they engage with platforms such as Google Classroom, Zoom, and Microsoft Teams. Findings reveal that while a majority of faculty members have access to internet and personal equipment, actual usage of digital tools remains uneven. The study identifies a moderate level of engagement with online teaching practices, with Zoom being the most widely used platform. However, fewer faculty members have taken initiative in designing digital classrooms or conducting online assessments. The results underscore the need for targeted professional development and institutional support to bridge the digital divide and enhance the effective use of technology in higher education. The study contributes to policy formulation and capacity-building strategies, aimed at fostering digital competence among college educators in the region.